Involvement and Targeted Intervention of Mortalin-Regulated Proteome Phosphorylated-Modification in Hepatocellular Carcinoma - Yang, Ye; Jin, Ming; Dai, Yi; Shan, Wenqi; Chen, Shuai; Cai, Rong; Yang, Haojun; Tang, Liming; Li, Lei (Frontiers in Oncology, 2021)
Objectives: To reveal the mechanisms of the effects of mortalin in hepatocellular carcinoma (HCC), and to identify potential novel chemical inhibitors of mortalin. Materials and Methods: For the experiments, three HCC cell lines (HepG2 cells, Hep3B cells, and sorafenib-resistant HuH7 cells) and xenografted nude mice were used. For the clinical analysis, cohorts of 126 patients with HCC and 34 patients with advanced recurrent HCC receiving sorafenib therapy were examined. Results: Mortalin regulated the phosphorylation-modification of cancer-associated proteins, and also regulated angiogenesis-related secretome to cause angiogenesis and sorafenib resistance in HCC cells. Two molecular mechanisms were identified. In one, via PI-3K/Akt signaling, mortalin regulated NF-κB, and then activated VEGF/VEGFR2 and GM-CSF, leading to the neovascularization. In the other, mortalin regulated PI-3K/Akt/β-catenin, then regulated Bcl-XL, Bcl-2, leading to the anti-apoptosis effect of HCC. Treatment of the sorafenib-resistant xenografts with sorafenib in combination with mortalin knockdown facilitated the sorafenib-mediated inhibition of tumor growth and angiogenesis, and increased apoptosis. Mortalin was a potential risk factor for HCC, predicting poor prognosis and sorafenib resistance. Finally, we showed that caffeic acid (CaA, C9H8O4) could bind to and induce the ubiquitination-mediated degradation of mortalin, which in turn blocked the above-mentioned signaling pathways, leading to the inhibition of angiogenesis and the reversal of sorafenib resistance. Conclusions: Mortalin, which regulates the phosphorylation of cancer-associated proteins, caused angiogenesis and sorafenib resistance, and was a competitive risk factor for HCC. Caffeic acid can therefore be considered as a novel chemical inhibitor that targets the action of mortalin, and a potential treatment for HCC.